Anatomical Variation in Maxillary Sinus Ostium Positioning: Implications for Nasal‐Sinus Disease. Issue 6 (13th December 2018) - Butaric, Lauren N.; Wadle, Michael; Gascon, Jemuel; ,
ABSTRACT: Among humans, superiorly located maxillary sinus ostia (MSO) result in drainage complications and maxillary sinus (MS) disease. While previous studies investigate maxillary sinusitis frequency or MSO‐position relative to specific nasal landmarks, few explore MSO‐position to overall MS dimensions. This study investigates whether MSO‐position relates to MS size/shape and if sex‐based differences exist. Twenty‐nine landmarks, placed on magnetic resonance images (MRIs) of 109 individuals (males = 57; females = 52), captured maximum dimensions of the cranium, MS, nasal cavity, and MSO‐position relative to the MS floor (MSO_MSF) and nasal floor (MSO_NCF). Landmark coordinates were used to calculate centroid sizes and 13 linear distances; distances were size standardized by cranial centroid‐size. Principal components analysis (PCA) on 3D‐coordinates indicates that variation in MSO‐position relates to superior–inferior MS positioning within the face (PC1 22% variance) and MS height (PC2 12% variance). Regression analyses indicate that MS size (r 2 = 0.502; P < 0.001) and height (r 2 = 0.589; P < 0.0001) strongly contribute to MSO_MSF: larger, taller MSs exhibit greater MSO_MSFs. Sex‐based differences were not evident in PC shape‐analyses nor among size‐standardized dimensions. However, Mann–Whitney U ‐tests indicate females have absolutely smaller MSs ( P = 0.001) and MSO_MSF distances ( P = 0.001). Further, regressions indicate females exhibit lower MSO_MSFs for a similar MS height. Overall, MSOs superiorly placed relative to the MS floor correlate with larger, taller MSs and/or sinuses positioned inferiorly within the face. While craniofacial surgeons/clinicians should be aware of potential sex‐based differences in MS size and MSO position, this study does not suggest that higher incidences of female‐reported sinusitis relate to sex‐based differences in MS anatomy. Anat Rec, 302:917–930, 2019. © 2018 Wiley Periodicals, Inc.